2018
DOI: 10.1007/s11618-018-0832-0
|View full text |Cite
|
Sign up to set email alerts
|

Instruktionssensitivität von Tests und Items

Abstract: Testergebnisse von Schülerinnen und Schülern dienen regelmäßig als ein zentrales Kriterium für die Beurteilung der Effektivität von Schule und Unterricht. Gültige Rückschlüsse über Schule und Unterricht setzen voraus, dass die eingesetzten Testinstrumente mögliche Effekte des Unterrichts auffangen können, also instruktionssensitiv sind. Jedoch wird diese Voraussetzung nur selten empirisch überprüft. Somit bleibt mitunter unklar, ob ein Test nicht instruktionssensitiv oder ein Unterricht nicht effektiv war. Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
2
0
2
Order By: Relevance
“…Die Bildungsstandards haben in den Ländern einen vergleichsweise engen Bezug zu den Lehrplänen und Curricula der Bundesländer (Ehmke et al 2017) und somit sehr wahrscheinlich auch zu den realisierten Lerngelegenheiten im Unterricht. Somit ist der BiSta-Test sensibler als der PISA-Test für das schulisch erworbene Wissen (Naumann 2019 (Guill et al 2010). Wie oben beschrieben, konnte zwar der bekannte Schereneffekt für die Mathematikleistung von der 4. zur 6.…”
Section: Kognitives Lernumfeldunclassified
“…Die Bildungsstandards haben in den Ländern einen vergleichsweise engen Bezug zu den Lehrplänen und Curricula der Bundesländer (Ehmke et al 2017) und somit sehr wahrscheinlich auch zu den realisierten Lerngelegenheiten im Unterricht. Somit ist der BiSta-Test sensibler als der PISA-Test für das schulisch erworbene Wissen (Naumann 2019 (Guill et al 2010). Wie oben beschrieben, konnte zwar der bekannte Schereneffekt für die Mathematikleistung von der 4. zur 6.…”
Section: Kognitives Lernumfeldunclassified
“…Educational effectiveness research regularly uses student test scores as dependent variables in statistical models (e. g., Klieme, 2018;Marsh et al, 2012). However, the assumption that the individual-level student outcome measures are indeed sensitive to classroom-level teaching is scarcely substantiated in effectiveness research, although researchers have regularly asserted the need for evidence of instructional sensitivity (e. g., Naumann, Musow, Aichele, Hochweber & Hartig, 2019;Popham, 2007). Recent studies have found the association of teaching measures and student achievement to vary across different tests (e. g., Grossman, Cohen, Ronfeldt & Brown, 2014;Polikoff, 2016).…”
Section: Validitymentioning
confidence: 99%
“…Educational effectiveness research regularly uses student test scores as dependent variables in statistical models (e. g., . However, the assumption that the individual-level student outcome measures are indeed sensitive to classroom-level teaching is scarcely substantiated in effectiveness research, although researchers have regularly asserted the need for evidence of instructional sensitivity (e. g., Naumann, Musow, Aichele, Hochweber & Hartig, 2019;Popham, 2007). Recent studies have found the association of teaching measures and student achievement to vary across different tests (e. g., Grossman, Cohen, Ronfeldt & Brown, 2014;Polikoff, 2016).…”
Section: Validitymentioning
confidence: 99%